Evaluasi Proses Pemilihan Vendor Paper Packaging Menggunakan Metode Analytical Hierarchy Process (AHP) Pada PT. XYZ - Gunawan, Azriel Revanza; Sasmita, Asep Hadian; Larutama, Wiku (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. XYZ is a trading company engaged in the multinational distribution of packaging products. To support the sustainability of its operations and performance, PT. XYZ is required to select vendors that can optimally meet its needs. However, in practice, the company does not yet have a standardized method or clear criteria for vendor selection, relying solely on price considerations. This condition may lead to inaccurate decision-making, which can negatively affect company performance. This study aims to evaluate the paper packaging vendor selection process at PT. XYZ using the Analytical Hierarchy Process (AHP) method. The results indicate that price is the most dominant criterion in the decision-making process, with a weight of 0.377. Among the five vendor alternatives analyzed, Vendor B was identified as the most suitable choice, with the highest priority weight of 0.232. These findings are expected to serve as a reference for the company in adopting a more structured and objective vendor selection process in the future.